2016
DOI: 10.4067/s0717-95022016000400008
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism Using the Interstyloid Distances and Clinical Implication for Elongated Styloid Process in Northeastern Thailand

Abstract: SUMMARY:Skeletal remains are crucial in forensic identification of the sex, especially human skulls including the styloid process, a bony projection from the skull. Hence, the objectives of the present study were undertaken to assess the value of the styloid process for the sex identification of unknown skulls and also to investigate the prevalence of elongated styloid process in 102 human dry skulls from the northeast Thai population. As a result, the interstyloid distances at both base and tip of the styloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Other studies had evaluated the SP elongation based on dry skulls, including Vadgaonkar et al [33] on indian, Sakaew el. [32] on Thai, Custodio et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies had evaluated the SP elongation based on dry skulls, including Vadgaonkar et al [33] on indian, Sakaew el. [32] on Thai, Custodio et al…”
Section: Discussionmentioning
confidence: 99%
“…[16] While many studies suggest that SP considered elongated when it is longer than 30 mm. [32,30,17,18]. Although, there is limited number of studies consider the SP elongated when it exceeds 45 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Custodio et al [ 1 ], Vadgaonkar et al [ 2 ], Natsis et al [ 32 ], Sakaew et al [ 33 ] evaluated SP elongation on dry skulls in Brazilian, Indian, Greek and Thai populations, respectively; other studies, such as that conducted by Kursoglu et al [ 4 ] on Turkish, More and Asrani [ 26 ] on Indian, Shaik et al [ 31 ] on Saudian and Al-Khateeb et al [ 34 ] on Jordanian populations were performed based on panoramic radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, i read the recent publication by Waraporn et al, on "Sexual Dimorphism Using the Interstyloid Distances and Clinical Implication for Elongated Styloid Process in Northeastern Thailand" with a great interest (Sakaew et al, 2016). Waraporn et al, noted that "it is suggested that the styloid process can be applied to the sex identification by measuring the interstyloid distance at the base or the tip of these processes" (Sakaew et al).…”
mentioning
confidence: 99%
“…Waraporn et al, did not exclude the cases with underling thalassemia and hemoglobinopathy. Anyone with thalassemia and hemoglobinopathy can have the bone problem (including the maxilla) (Di Matteo et al, 2008) and this can be the missed uncontrolled confounding factor in the study by Waraporn et al He leído con gran interés la reciente publicación de Waraporn et al, titulada "El Dimorfismo Sexual Utilizando las Distancias Interestiloides y la Implicación Clínica para el Proceso Estiloides Elongado en el Noreste de Tailandia" (Sakaew et al, 2016). Waraporn et al señalan "se sugiere que el proceso estiloideo puede aplicarse a la identificación del sexo mediante la medición de la distancia interestiloide en la base o en la punta de estos procesos" (Sakaew et al).…”
unclassified